PERSEPSI MAHASISWA PGMI TERHADAP PENERAPAN METODE PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN MICROTEACHING - Oktarina, Elsi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the perceptions of students in the Islamic Elementary Teacher Education (PGMI) program regarding the implementation of the Problem Based Learning (PBL) method in microteaching instruction. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations of microteaching activities, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings show that students have positive perceptions of the implementation of PBL. PBL is considered effective in enhancing students’ understanding of lesson planning, developing collaboration and communication skills, and increasing their confidence when conducting microteaching. Nevertheless, students also encountered several challenges, such as limited time, the complexity of PBL stages, and the need for more intensive guidance from lecturers. Overall, PBL is viewed as effective in supporting the development of pedagogical and professional competencies of PGMI students in the context of microteaching.